2019
DOI: 10.3390/molecules24193438
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Catalysts for Ozone Processes to Decontaminate Water

Abstract: The use of graphene-based materials as catalysts in both ozone and ozone/radiation processes is creating interest among researchers devoted to the study of advanced oxidation processes (AOPs) for the degradation of organic pollutants in water. In this review, detailed explanations of catalytic and photocatalytic ozonation processes mediated by graphene-based materials are presented, focusing on aspects related to the preparation and characterization of catalysts, the nature of the water pollutants treated, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 117 publications
0
5
0
Order By: Relevance
“…The traditional method to generate hydrogen usually results in high emissions of CO 2 ; thus, it is essential to develop a sustainable and scalable method. For example, in the conventional steam methane reforming process, approximately 12 kg of CO 2 is exhausted per 1 kg of H 2 . , In PR, to produce hydrogen, photogenerated electrons react with the adsorbed H + to produce H 2 . , It is worth mentioning that H 2 production originates from water instead of from the organic substrate, using the mass spectrometry analysis in deuterated and nondeuterated solvents ,, Uekert et al . have shown that the H 2 yield of 11.4 ± 1.2 μmol g –1 is achieved after 5 days of reaction from a grounded commercial PET bottle over a carbon nitride/nickel phosphide PC.…”
Section: Photoreforming Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional method to generate hydrogen usually results in high emissions of CO 2 ; thus, it is essential to develop a sustainable and scalable method. For example, in the conventional steam methane reforming process, approximately 12 kg of CO 2 is exhausted per 1 kg of H 2 . , In PR, to produce hydrogen, photogenerated electrons react with the adsorbed H + to produce H 2 . , It is worth mentioning that H 2 production originates from water instead of from the organic substrate, using the mass spectrometry analysis in deuterated and nondeuterated solvents ,, Uekert et al . have shown that the H 2 yield of 11.4 ± 1.2 μmol g –1 is achieved after 5 days of reaction from a grounded commercial PET bottle over a carbon nitride/nickel phosphide PC.…”
Section: Photoreforming Technologymentioning
confidence: 99%
“…73,74 In PR, to produce hydrogen, photogenerated electrons react with the adsorbed H + to produce H 2 . 75,76 It is worth mentioning that H 2 production originates from water instead of from the organic substrate, using the mass spectrometry analysis in deuterated and nondeuterated solvents 20,68,76 Uekert et al 20 have shown that the H 2 yield of 11.4 ± 1.2 μmol g −1 is achieved after 5 days of reaction from a grounded commercial PET bottle over a carbon nitride/nickel phosphide PC. The production activity increases up to 4.13 ± 0.40 mmol g −1 h −1 using CdS as PC.…”
Section: Photoreforming Technologymentioning
confidence: 99%
“…Therefore, industrial dye wastewater treatment has received much attention. Among numerous pollutant treatment approaches, photocatalysis is one of the most promising methods for wastewater treatment [2][3][4]. In recent years, Bi-based photocatalysts have attracted much attention [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene discovered in 2004-a 2D material with significant optical, conductivity, and electronic properties, among others [22]-is also investigated. TiO 2 doping with graphene oxide, confers it the possibility of reducing the band gap and, hence, the increase of visible light absorption [23]. Additionally, some works have already been published on the use of UVA or visible light emitting diodes (visLED) to substitute artificial UV lamps [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, few works deal with studies on the kinetics of the process. In many cases, the kinetics are oversimplified just determining pseudo first order rate constants [23,[31][32][33][34]. Other investigations are limited to find out through which mechanism the oxidation occurs, different scavengers that react with reactive oxygen species (ROS)-such as hydroxyl radicals, singlet oxygen, positive holes in the valence band, etc.-are therefore applied [27,35].…”
Section: Introductionmentioning
confidence: 99%